Experimental evidence for indirect facilitation among invasive plants. (3rd December 2013) - Flory, S. Luke; Bauer, Jonathan T.; Buckley, Yvonne
Summary Facilitation among species may promote non‐native plant invasions through alteration of environmental conditions, enemies or mutualists. However, the role of non‐trophic indirect facilitation in invasions has rarely been examined. We used a long‐term field experiment to test for indirect facilitation by invasions of Microstegium vimineum (stiltgrass) on a secondary invasion of Alliaria petiolata (garlic mustard) by introducing Alliaria seed into replicated plots previously invaded experimentally by Microstegium. Alliaria more readily colonized control plots without Microstegium but produced almost seven times more biomass and nearly four times as many siliques per plant in Microstegium‐invaded plots. Improved performance of Alliaria in Microstegium‐invaded plots compared to control plots overwhelmed differences in total number of plants such that, on average, invaded plots contained 327% greater total Alliaria biomass and 234% more total siliques compared to control plots. The facilitation of Alliaria in Microstegium‐invaded plots was associated with an 85% reduction in the biomass of resident species at the peak of the growing season and significantly greater light availability in Microstegium‐invaded than control plots early in the growing season. Synthesis. Our results demonstrate that an initial plant invasion associated with suppression of resident species and increased resource availability can facilitate a secondary plant invasion. Such positive interactions among species with similar habitat requirements, but offset phenologies, may exacerbate invasions and their impacts on native ecosystems.